Mass Media Variables for Anticipating Creativity among Academically Bright Rural Adolescents - Sheoran, Sumit; Dhanda, Bimla; Malik, Joginder Singh (Indian Journal of Extension Education, 2025)
Creativity is the tendency to generate ideas, alternatives and possibilities that may assist in encountering day to day life problems, communicating with others and entertainingÂ ourselves and others whereas media technologies act as a medium while interacting with a large group of audience via mass communication. The study explored the relationshipÂ between mass media use and creativity. The primary data collected from 300 participants included independent variables related to mass media used, time spend and the social mediaÂ use. Five aspects of creativity i.e., seeing problem, unusual uses fluency, unusual uses flexibility, unusual uses originality and unusual uses creativity were used. Chi-squareÂ analysis indicated that social media use was significantly associated with the all aspects of unusual uses of creativity of respondentsâ€™ i.e., fluency, flexibility, originality and creativity.Â It was elucidated that the amount of time spend on mass media was significantly associated with adolescentsâ€™ seeing problem abilities and their unusual uses fluency. No association wasÂ observed between type of mass media used by participants and their creative abilities.